Taxonomic review of the species of Parkinsonia (Leguminosae, Caesalpinioideae) from the Americas - Romão,Marcos Vinicius Varjão (2021)
Abstract The genus Parkinsonia has a pantropical distribution with 12 species globally, occurring mainly in arid and semi-arid climate environments. Many taxonomic studies have considered Parkinsonia as a distinct genus of Cercidium, but phylogenetic analyses do not support this distinction because, when together, they form a well-supported monophyletic group. The aim of this study was to review the taxonomy of Parkinsonia species from the Americas. We examined 400 specimens deposited in herbaria, original diagnoses, and types. We present here morphological descriptions, identification key, taxonomic notes and nomenclatural notes, ecology and conservation status, reproductive phenological states, distribution maps and drawings for each species in this treatment. Our study points out eight species of Parkinsonia for the Americas (P. aculeata, P. andicola, P. florida, P. glauca, P. microphylla, P. peruviana, P. praecox, and P. texana), three new synonyms of Parkinsonia (Cercidium macrum, P. inermis, and P. texana var. macra) and six new lectotypifications (Cercidium plurifoliolatum, C. spinosum, P. inermis, P. microphylla, P. praecox, P. texana). The main diagnostic characteristics are green or gray stem, branches generally with thorns, reduced leaves (pinnate appearance) or not reduced (bipinnate), hyphodromous venation, racemose inflorescences, yellow petals and moniliform or flat pod fruit.